(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Due to the increasing interest in the quality of auditing by writers, researchers and regulators of the auditing profession. The matter necessitated a statement of the extent to which the auditor practices professional skepticism, because of its significant impact in discovering errors and material misrepresentations contained in the financial statements in order to give the financial community confidence in them and the success of the audit process. The research aims to clarify the concept and importance of the practice of professional skepticism and its effect on the quality of the auditor’s performance in Iraq. To achieve the research objectives, the two researchers prepared a questionnaire according to the five-point Likert scale. In their preparation, they took into account the compatibility with the characteristics of the study community, and that the target research community is represented by auditors. Employees of the Federal Office of Financial Supervision and auditors working in private auditing companies and offices, as well as academics specialized in this field. The researchers reached conclusions, the most important of which was that the practice of professional skepticism leads to an increase in the quality of the auditor’s performance by discovering errors and material misrepresentations resulting from fraud. The most important recommendations reached by the two researchers is the need to oblige the auditor to apply the characteristics of professional skepticism when auditing financial statements, as they have a significant impact on the issuance of his professional judgment, and thus improve the quality of his performance